2014
DOI: 10.1007/s12355-014-0334-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential Induction of 3-deoxyanthocyanidin Phytoalexins in Relation to Colletotrichum falcatum Resistance in Sugarcane

Abstract: Sugarcane secrets a reddish pigment presumed to contain phytoalexin compounds in the stalk tissues in response to infection of Colletotrichum falcatum, causing red rot. To identify the phytoalexin compounds involved in red rot resistance, detailed HPLC analyses were conducted using the phytoalexin standards in a set of sugarcane cultivars varying in red rot resistance, after pathogen inoculation. We found nine different 3-deoxyanthocyanidin phytoalexin compounds, which are differentially induced upon C. falcat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The accumulation of 3-deoxyanthocyanidin in sugarcane has been identified to strengthen the resistance to the red rot pathogen Colletotrichum falcatum [ 19 ]. Ganesh et al used HPLC analysis to reveal the mechanism of nine 3-deoxyanthocyanidin compounds against Colletotrichum falcatum resistance differentially from different sugarcane cultivars [ 20 ]. Ganesh et al revealed the mechanism of differential expression of key genes in the anthocyanin metabolic pathway by studying the antifungal properties of 3-deoxyanthocyanidin [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of 3-deoxyanthocyanidin in sugarcane has been identified to strengthen the resistance to the red rot pathogen Colletotrichum falcatum [ 19 ]. Ganesh et al used HPLC analysis to reveal the mechanism of nine 3-deoxyanthocyanidin compounds against Colletotrichum falcatum resistance differentially from different sugarcane cultivars [ 20 ]. Ganesh et al revealed the mechanism of differential expression of key genes in the anthocyanin metabolic pathway by studying the antifungal properties of 3-deoxyanthocyanidin [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total 3-Deoxyanthocyanidin Content (TDC). The TDC was measured by reading the absorbances of redissolved extracts at 480 nm, and was expressed as milligrams of 3-deoxyanthocyanidin /g DE flour, using the molar extinction coefficient of luteolinidin, which is 13,800 M -1 cm -1 (Kumar et al, 2015). Phytate content.…”
Section: Chemical Analysesmentioning
confidence: 99%